Pemeriksaan Golongan Darah Dan Rhesus Pada Anak Sekolah Dasar (SD) Dan Pendidikan Anak Usia Dini (PAUD) Di Desa Bone Kecamatan Nekamese Kabupaten Kupang - Agnes Rantesalu; Marni Tangkelangi; Novelia G.B. So’o; Novian Yudaswara; Aldiana Astuti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Bone Village is a fostered village of the TLM Study Program, Poltekkes, Kupang Ministry of Health, which is in the Nekamese sub-district, Kupang district. This village has an early childhood education center and a Elementary School (SD). On average, PAUD students will have their blood type checked when they are about to enter the next stage of school, namely elementary school, because blood type is one of the requirements for enrolling in elementary school, while those who do not continue their studies will not have the opportunity to have their blood group checked. SD Negri Bone students rarely have their blood group or rhesus checked, so it is deemed necessary to do a blood group examination for elementary school and PAUD children. The output of this activity is that elementary and early childhood students in Bone Village know about the importance of golda and know each other's golda. The results showed that the respondents were elementary school students (68.6%) while those in early childhood education (31.4%). The highest grade of elementary school children was found in grade B+ (24.2%) and grade O+ (24.2%). In the golda of PAUD children the most was in golda B+ (14.1%).